Spectroscopic and microcalorimetric studies on the molecular binding of food colorant acid red 27 with deoxyribonucleic acid. Issue 8 (5th February 2016) - Basu, Anirban; Kumar, Gopinatha Suresh
Abstract : Interaction of the food colorant acid red 27 with double stranded DNA was investigated using spectroscopic and calorimetric methods. Absorbance and fluorescence studies suggested an intimate binding interaction between the dye and DNA. The quantum efficiency value testified an effective energy transfer from the DNA base pairs to the dye molecules. Minor groove displacement assay with Hoechst 33258 revealed that the binding occurs in the minor groove of DNA. Circular dichroism studies revealed that acid red 27 induces moderate conformational perturbations in DNA. Results of calorimetric studies suggested that the complexation process was driven largely by positive entropic contribution with a smaller favorable enthalpy contribution. The equilibrium constant of the binding was calculated to be (3.04 ± 0.09) × 10 4 M −1 at 298.15 K. Negative heat capacity value along with the enthalpy–entropy compensation phenomenon established the involvement of dominant hydrophobic forces in the binding process. Differential scanning calorimetry studies presented evidence for an increased thermal stability of DNA on binding of acid red 27. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The binding of the food colorant acid red 27 with double stranded DNA was studied using multiple spectroscopic and microcalorimetric techniques. Acid red 27 was found to bind in the minor grooves of DNA. Isothermal titration calorimetric studies suggested that the binding was favored largely by positive entropic contribution, while differential scanning calorimetric studies revealed that acid red 27 stabilized the DNA against thermal denaturation.